Capitalizing on the Valences of the Internal Audit in Achieving a Reliable and Efficient Financial-Accounting System: Array - Soare, Janina; Dănescu, Magdalena (Acta Universitatis Danubius. Œconomica, 2021)
Manifestation of the internal audit on the financial-accounting activity means: ensuring the achievement of the established specific objectives; timely identification of risks that may occur and making recommendations for their management; streamlining the financial-accounting activity by identifying new ways of carrying out the activities faster, with less resources, with the adequate specialization of the staff and with the increase of the performances.